Prognosis and chemosensitivity of deficient MMR phenotype in patients with metastatic colorectal cancer: An AGEO retrospective multicenter study. Issue 1 (13th February 2020) - Tougeron, David; Sueur, Benjamin; Zaanan, Aziz; de la Fouchardiére, Christelle; Sefrioui, David; Lecomte, Thierry; Aparicio, Thomas; Des Guetz, Gaetan; Artru, Pascal; Hautefeuille, Vincent; Coriat, Romain; Moulin, Valerie; et al.
Abstract : Mismatch repair‐deficient (dMMR) and/or microsatellite instability‐high (MSI) colorectal cancers (CRC) represent about 5% of metastatic CRC (mCRC). Prognosis and chemosensitivity of dMMR/MSI mCRC remain unclear. This multicenter study included consecutive patients with dMMR/MSI mCRC from 2007 to 2017. The primary endpoint was the progression‐free survival (PFS) in a population receiving first‐line chemotherapy. Associations between chemotherapy regimen and survival were evaluated using a Cox regression model and inverse of probability of treatment weighting (IPTW) methodology in order to limit potential biases. Overall, 342 patients with dMMR/MSI mCRC were included. Median PFS and overall survival (OS) on first‐line chemotherapy were 6.0 and 26.3 months, respectively. For second‐line chemotherapy, median PFS and OS were 4.4 and 21.6 months. Longer PFS (8.1 vs . 5.4 months, p = 0.0405) and OS (35.1 vs . 24.4 months, p = 0.0747) were observed for irinotecan‐based chemotherapy compared to oxaliplatin‐based chemotherapy. The association was no longer statistically significant using IPTW methodology. In multivariable analysis, anti‐VEGF as compared to anti‐EGFR was associated with a trend to longer OS (HR = 1.78, 95% CI 1.00–3.19, p = 0.0518), whatever the backbone chemotherapy used. Our study shows that dMMR/MSI mCRC patients experienced short PFS with first‐line chemotherapy with or without targeted therapy. OS was not different according to the chemotherapy regimen used, but a trend to better OS was observed with anti‐VEGF. Our study provides some historical results concerning chemotherapy in dMMR/MSI mCRC in light of the recent nonrandomized trials with immune checkpoint inhibitors. Abstract : What's new? Some reports suggest short overall survival (OS) and chemoresistance of mismatch repair‐deficient and/or microsatellite instability‐high metastatic colorectal cancers (dMMR/MSI mCRC). In a large multicenter series of dMMR/MSI mCRC we observed a relatively long OS but short progression‐free survival. Irinotecan‐based chemotherapy was not associated with better OS than oxaliplatin‐based chemotherapy but anti‐VEGF, as compared to anti‐EGFR, was associated with a trend to longer OS. These results could help clinicians to choose treatment in patients with dMMR/MSI mCRC.